Duchenne expert physician perspectives on Duchenne newborn screening and early Duchenne care. Issue 2 (5th August 2022) - Armstrong, Niki; Schrader, Rachel; Fischer, Ryan; Crossnohere, Norah
Abstract: Duchenne muscular dystrophy (DMD) is a progressive, fatal neuromuscular disorder typically diagnosed between 4 and 5 years of age. DMD currently has five FDA approved therapies, which has led to increased interest in newborn screening (NBS) for DMD. Our objective was to explore the perspectives and predicted practices of physicians (primarily neurologists) who will likely be responsible for the follow‐up of infants identified with DMD through NBS. A short survey was developed and distributed to physicians who are responsible for providing care for patients with Duchenne at Certified Duchenne Care Centers across the USA. Twenty‐seven physicians responded to statements about benefit and readiness for dystrophinopathy NBS, which care recommendations they would make at initial infant visits, and when they would recommend initiating approved therapies. Most DMD physicians indicated they see benefit in NBS (82%) and believe the DMD care community is ready for NBS in dystrophinopathies (74%). The majority of physicians would recommend multiple interventions, including genetic counseling, maternal carrier testing, referral to early intervention services, screening siblings, discussion of clinical trials, exon skipping therapies, and assessment of social and language development at initial visits. The majority of physicians also indicated they would recommend initiating approved therapies much earlier than the typical age of diagnosis.